The Personal and Business Qualities Features of Police Officers Who Quit in the First Year of Professional Activity - N.V. Martirosova; Y.A. Korneeva; A.V. Korneeva (Moscow State University of Psychology and Education, 2023)
In the article pursuant to the resolution of the Russian Federation of December 6, 2012, No. 1259 “Approval of the internal affairs bodies of the Russian Federation” psychologists within the framework of professional psychological selection, highlighted the most important personal and business qualities of employees. The research materials were collected as part of a joint research project of the region, 634 employees of the office management service in the internal authorities of the Arkhangelsk region took part. Personal and business qualities, measured by means of basic psychological tests, are regulated by the use of a selection procedure in internal affairs. Police officers who quit in the first year of professional activity are distinguished by a reduced level of legal awareness, lower intellectual properties and internality, a predominance of the need for good working conditions, a reduced need for achievements, self-improvement, and interesting and useful work.